Pengaruh Variabel Makro Ekonomi Terhadap Indeks Jakarta Islamic Index (JII) Periode Januari 2010 Hingga November 2015 - Ayu Tri Utami; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The study aimed to know whether there were influences of inflation, interest rate, and exchange rate on the Jakarta Islamic Index (JII). The study population were factors which influenced the Jakarta Islamic Index. The sample were those factors in the period of January 2010- November 2015. Multiple linear regression was used for the analysis. The analysis showed that inflation had a negative effect on Jakarta Islamic Index (JII) index, interest rates had a positive effect on Jakarta Islamic Index (JII) index, and the exchange rate had a positive effect on Jakarta Islamic Index (JII) index. All independent variables simultaneously had an effect on the Jakarta Islamic Index (JII) index. This study was expected to add insightsto science, governance and other fields.